Niche divergence among closely related taxa provides insight on evolutionary patterns of ticks - Cuervo, Pablo Fernando (2021)
Aim: Understanding the degree to which closely related taxa diverge in their niche traits could provide insight on their evolutionary patterns, as well as shed some light on the mechanisms underpinning broad-scale biogeographic patterns. The evolution of ticks was thought to be driven by hosts. However, recent evidence suggests that tick evolution is more likely to be driven by habitat conditions. The Amblyomma maculatum group of ticks provides a good example to test the former, as its incipient speciation raises the possibility of a very rapid adaptation to slightly different environments. Location: The Americas. Taxa: Ticks from the Amblyomma maculatum Koch, 1844 (Acari: Ixodidae) group (A. tigrinum, A. triste s.s., A. maculatum s.s. and two intermediate morphs). Methods: We addressed the question of whether the differentiation of taxa within this group results from ecological factors, either maintaining a similar ecological niche (conservatism) or by occupying distinct niches (divergence). We analysed the distribution of each tick morphotype with ecological niche models. Next, we explored the question of whether these closely related taxa inhabit environments that are more different or more similar than expected by comparing niche overlap in environmental space. Results: We found evidence for niche differentiation, showing that the members of the Amblyomma maculatum group exist in and respond to aspects of different environments, leading to geographical variation. Main conclusions: The analysis of the ecological niches of the Amblyomma maculatum group of ticks indicates niche conservatism for the pairs A. tigrinum—A. maculatum s.s. and A. triste s.s.—A. maculatum s.s, traditionally associated to allopatric speciation; while incipient niche divergence is suggested for the remaining comparisons. These findings add additional evidence to the study of the evolution of ticks, giving support to the hypothesis of habitat conditions driving the evolution of taxa with no strict host specificity.